The Impact of the Pancasila Student Profile Strengthening Project (P5) on the Entrepreneurial Spirit of Seventh-Grade Students at SMP Negeri 2 Kubung - Alfatihah, Mardia; Desi Armi Eka Putri; Ikhwan (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study is motivated by the low interest of seventh-grade students at SMP Negeri 2 Kubung in entrepreneurship activities. Most students participate in these activities merely to fulfill school assignments, rather than due to personal motivation or genuine interest in entrepreneurship. This condition has the potential to hinder the development of an entrepreneurial mindset, which should be one of the essential competencies in 21st-century education. The purpose of this study is to determine the extent of the influence of the implementation of the Projek Penguatan Profil Pelajar Pancasila (P5) on the entrepreneurial spirit of seventh-grade students at SMP Negeri 2 Kubung. This study employs a quantitative approach with an associative research design. The research population consists of all seventh-grade students in the 2024/2025 academic year, totaling 111 students, with a sample of 87 students selected using simple random sampling. Data analysis was conducted using simple linear regression analysis. The results indicate that the implementation of P5 has a significant effect on students’ entrepreneurial spirit, with a significance value of 0.00 < 0.05 and a calculated t-value of 5.284 > the t-table value of 1.666. The magnitude of the influence of P5 implementation on the entrepreneurial spirit is 24.7%. Thus, it can be concluded that the better the implementation of the Projek Penguatan Profil Pelajar Pancasila, the higher the students’ entrepreneurial spirit